Caracterizaçăo clínica e demográfica de pacientes com doença falciforme acompanhados na Fundaçăo Hospitalar de Hematologia e Hemoterapia do Amazonas - HEMOAM - Cesar, Purim (2017)
Sickle cell disease (SCD) is an autosomal recessive disease characterized by the inheritance of a homozygous mutation in the beta globin gene (HBB), that causes replacement of glutamic acid at position 6 of the beta globin chain by valine. This alteration results in formation of an abnormal hemoglobin (HbS), which in deoxygenated form undergoes polymerization leading to sickling of red blood cells. Clinically SCD is characterized by painful seizures caused by vaso-occlusion in the microcirculation resulting in acute and chronic lesions in various organs and tissues such as heart, lungs, bones, kidneys, liver, retina and skin. In addition, patients with SCD are more susceptible to bacterial infections due to splenic dysfunction secondary to multiple infarctions, which often leads to functional asplenia or autosplenectomy. SCD is today seen essentially as an inflammatory disease secondary to the vaso-occlusion process. This makes the effect of other genetic traits that modulate the inflammatory response in SCD’s clinical presentation relevant. Recently prediction of the SCD has improved significantly, thanks to early diagnosis through neonatal screening, improvement of treatment centers, systematic use of blood products and iron chelators, as well as treatment with hydroxyurea. These new developments have improved the quality of life of the patients reducing the number of critical cases and hospitalizations. Despite all the new available therapies, the level of attention and the therapeutic options are still insufficient, since most of the patients suffer from serious complications of the disease. In the Amazon region, patients with SCD are attended and assisted at HEMOAM Foundation, Manaus. However, the clinical characteristics of the SCD patients attending HEMOAM is still unknown. Hence, the present study was undertaken to characterize clinical and demographic aspects of SCD patients attending HEMOAM foundation with the goal of identifying clinical aspects peculiar to this population, as well as providing data for a better planning of assistance for these patients by the public health managers. The study was crosssectional observational, without intervention. The study population consisted of 122 patients who were recruited from a total of 236 individuals registered in the institution's historical record. Of these, 89.7% were homozygous for the presence of HbS (SS), while the rest were presenting other forms of SCD. The mean age of the population was 15 years and the distribution among male and female was 52:70. No significant differences were observed regarding to access to treatment for SCD, although we have observed that patients who live in the interior have been diagnosed later than those who live in Manaus. About the clinical presentation, the most 6 frequent complication was the lower limb ulcers, reported in 84.5% of patients. The severity of the SCD, estimated by a internationally validated.The total of our patients is divided into three groups: 2 to 17 years; 18 to 40 years; And greater than 40 years. Using this division, the severity scores in our population were 0.34 (0.04-0.89) in patients younger than 18 years, 0.63 (0.20- 0.96) in patients between 18 -40 Years, and 0.80 (0.71-0.97) in patients older than 40 years,in our population similar to the severity score of the patient population from Rio de Janeiro. The results obtained allowed us to obtain a comprehensive profile of the demographic, social and clinical characteristics of SCD in Amazonas, and will be important for the planning assistance to SCD patients. In addition, we were able to observe the impact of socioeconomic aspects on care, while showing that essential aspects of SCD treatment seem to be preserved in this population. Finally, the use of the severity score allowed us to obtain a general clinical picture of the evolution of SCD in a population with distinct ethnic characteristics from other SCD populations.